First order parallel coupled BPF with wideband rejection based on SRR and CSRR - Zaid A. Abdul Hassain; Amer Abbood AL-Behadili; Adham R. Azeez (Universitas Ahmad Dahlan, 2019)
In this paper a new approach for first order Chebyshev parallel coupled Bandpass filter resonant at 1 GHz is presented to obtain better results (wideband rejection, high selectivity and low bandpass insertion loss) compared to conventional design. The proposed filter (a tri-formation consisting of CSRR, SRR and stubs of stepped impedance are loaded microstrip resonator) can be configured, by laying split ring resonator (SRR) and complementary split ring resonator (CSRR) with 50 Ω microstrip lines, in addition to effect of loading two stubs of stepped impedance around center of midline microstrip with impedance line 55.36 Ω of parallel coupled. The proposed filter produces high selectivity from passband to stopband transition equals to 307.5 dB/GHz and an excellent wide stopband performance extend from 1.22 GHz to 5 GHz (harmonics repression till for 5 ƒ0); all are bellow -20 dB excepting one transmission zero of -19 dB, that can be eliminate the harmonic superior frequencies without using any external Bandstop filter. Also, enhancement low bandpass insertion loss level, where it reaches 0.25 dB at fundamental centered frequency (ƒ0 = 0.96 GHz) with 21% bandwidth. The proposed filter is designed and simulated with computer aided of Ansoft HFSS software package which ordinarily used in microwave application.